Evaluation of the Influence of Additional Beam Filtration on Image Quality and Patient Dose in X-ray Fluoroscopy Procedures - Ngaile, Justin; Msaki, Peter; Kazema, Ramadhani; Mwimanzi, Jerome; Mango, Mechris (Tanzania Journal of Science, 2021)
The aim of the study was to evaluate the influence of additional filtration on radiation dose and image quality for patients during hysterosalpingography (HSG) and retrograde urethrography (RUG) procedures. The influence of filtering on image quality for each phantom thickness was made using a combination of different filter thicknesses. Entrance surface air kerma (ESAK) rates to Perspex phantom were measured using a solid state detector for various added combination of filter materials. Fluoroscopic image contrast was assessed using a Leeds TOR-18FG test object with a range of filter materials and phantom thicknesses. Phantom studies demonstrated that the use of additional filter materials of up to 0.35 mm thickness of copper could be used without significant effect on the image quality. ESAK values were determined for 16, 20, 24 and 28 cm phantom. Phantom ESAK reduced by 63%, 63%, 64% and 65% for 16, 20, 24 and 28 cm, respectively, when using 0.35 mm Cu + 1 mmAl, without degrading image contrast. Three independent radiologists perceived no change in clinical image quality with added filtration. On adding 0.35 mm Cu and 1 mm Al, the KAP per examination for the HSG was reduced by 71%, while for the RUG was reduced by 75%. Key words: Additional filtration; image quality; patient dose; X-ray fluoroscopy procedures